Pelatihan dan Penguatan Komunikasi Kepada Kelompok Tani Tentang Pembibitan Sawit Bersertifikasi - Rosliana Lubis; Effiati Juliana Hasibuan; Ahmad Prayudi; Affandi Affandi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community service activity aims to provide training and strengthen communication to farmer groups about certified oil palm nurseries. The activity partner is a farmer group (Poktan) Putra Mandiri of Gunung Ambat village, Sei Bingai District, Langkat Regency, North Sumatra. The productivity of oil palm fresh fruit bunches (FFB) in this village is still low because the oil palm seeds used are